Vestibular Organ and Cochlear Implantation–A Synchrotron and Micro-CT Study - Li, Hao; Schart-Moren, Nadine; Rajan, Gunesh; Shaw, Jeremy; Rohani, Seyed Alireza; Atturo, Francesca; Ladak, Hanif M.; Rask-Andersen, Helge; Agrawal, Sumit (Frontiers in Neurology, 2021)
Background: Reports vary on the incidence of vestibular dysfunction and dizziness in patients following cochlear implantation (CI). Disequilibrium may be caused by surgery at the cochlear base, leading to functional disturbances of the vestibular receptors and endolymphatic duct system (EDS) which are located nearby. Here, we analyzed the three-dimensional (3D) anatomy of this region, aiming to optimize surgical approaches to limit damage to the vestibular organ. Material and Methods: A total of 22 fresh-frozen human temporal bones underwent synchrotron radiation phase-contrast imaging (SR-PCI). One temporal bone underwent micro-computed tomography (micro-CT) after fixation and staining with Lugol's iodine solution (I2KI) to increase tissue contrast. We used volume-rendering software to create 3D reconstructions and tissue segmentation that allowed precise assessment of anatomical relationships and topography. Macerated human ears belonging to the Uppsala collection were also used. Drilling and insertion of CI electrodes was performed with metric analyses of different trajectories. Results and Conclusions: SR-PCI and micro-CT imaging demonstrated the complex 3D anatomy of the basal region of the human cochlea, vestibular apparatus, and EDS. Drilling of a cochleostomy may disturb vestibular organ function by injuring the endolymphatic space and disrupting fluid barriers. The saccule is at particular risk due to its proximity to the surgical area and may explain immediate and long-term post-operative vertigo. Round window insertion may be less traumatic to the inner ear, however it may affect the vestibular receptors.